Switching from atorvastatin to rosuvastatin lowers small, dense low-density lipoprotein cholesterol levels in Japanese hypercholesterolemic patients with type 2 diabetes mellitus. (January 2016) - Bando, Yukihiro; Toyama, Hitomi; Kanehara, Hideo; Hisada, Azusa; Okafuji, Kazuhiro; Toya, Daisyu; Tanaka, Nobuyoshi
Highlights: Small dense LDL-cholesterol (sd LDL-C) levels without high LDL-C levels are involved in the development of arteriosclerosis due to lipid abnormalities in patients with type 2 diabetes mellitus. 129 subjects among a total of 230 outpatient subjects with T2DM who were currently receiving 10 mg atorvastatin once daily for ≥24 weeks were detected sd LDL-C using the LipoPhor AS ® system. Switching from 10 mg atorvastatin to 5 mg rosuvastatin exhibited a statistically significant reduction from baseline of sd LDL-C levels. Abstract: Aims: This open-label, randomized, parallel-group comparative study compared the efficacy of rosuvastatin (5 mg/day) and atorvastatin (10 mg/day) for reduction of small dense low-density lipoprotein cholesterol (sd LDL-C) levels in Japanese patients with type 2 diabetes mellitus (T2DM). Methods: Patients with T2DM and hypercholesterolemia with detectable sd LDL-C after receiving 10 mg/day atorvastatin for ≥24 weeks were randomly assigned to receive rosuvastatin (5 mg/day; switched treatment) or atorvastatin (10 mg/day; continued treatment) for 12 weeks. The primary endpoints were changes in sd LDL-C levels and sd LDL-C/total LDL-C ratio evaluated using the LipoPhor AS ® system. Results: There were no significant percent changes from baseline for LDL-C levels between the switched ( n  = 55) and the continued treatment group ( n  = 56). However, the former group exhibited a statistically significant reduction from baseline of sd LDL-C levels, sd LDL-C/total LDL-C ratio compared with the latter group (−3.8 mg/dL vs. −1.4 mg/dL, p  = 0.014; −2.3% vs. −0.6%, p  = 0.004, respectively). Multiple regression analysis among all subjects revealed that independent factors contributing to the reduction in sd LDL-C levels were a change in LDL-C ( p  = 0.003) and triglyceride (TG) levels ( p  = 0.006), treatment group (the switched group = 1, the continued group = 0; standard coefficient = −1.2, p  = 0.034) and baseline glycated hemoglobin A1c (HbA1c) ( p  = 0.045), respectively. Conclusion: Switching from 10 mg atorvastatin to 5 mg rosuvastatin may be a useful therapeutic option to reduce sd LDL-C levels in Japanese hypercholesterolemic patients with T2DM.